CONSUMER CONSIDERATIONS IN BUYING A HOME IN URBAN CITIES - Bagus Siahaan (Inovasi, 2022)
The rapid population growth in urban cities has mushroomed the housing business, including in the city of South Tangerang. As a buffer city for the capital city, South Tangerang is an option for urban communities to live/settle. This is an opportunity for housing businesses to be able to take advantage of this opportunity by offering profitable housing for consumers, such as strategic locations (close proximity and access to adequate mobility). In line with this explanation, the purpose of this study is to determine consumer buying interest based on housing location considerations. The object of this research is the Vinus 88 Residences housing which was built by PT Multi Sarana Satria. The research subjects are consumers who have bought a house, totaling 100 respondents. This research was conducted primarily by distributing questionnaires. Because the research uses a quantitative approach, the data collected will be processed using statistical regression techniques through the SPSS application. The results of the study show that the location factor is a priority factor for urban communities. This is motivated by considerations of work location or distance from home to workplace. Therefore, housing with a strategic location, which is close and has adequate vehicle access, will be more desirable to buy.Keywords: Housing, Urban City, Buying Interest, Strategic Location